UPPER QUATERNARY EVOLUTION OF THE NORTHERN ARGOLIS GULF, NAFPLIO AREA - Mitropoulos, D.; Zananiri, I. (Bulletin of the Geological Society of Greece, 2010)
The recent palaeogeographic history of the Gulf of Argolis was studied by means of marine geophysical surveys and sediment sampling for subsequent laboratory analyses. Data interpretation suggests a relatively smooth seafloor gradient, characterized by an amphitheatrical pattern of the sea bottom. Prominent beetling features comprise the Bourtzi islet near Nafplio coast, small ridges in the southern margin of the studied area, and several conical ridges in the central part of the gulf. Four unconformities were identified, defining four different sedimentary units. Granulometry measurements allowed the mapping of present-day seafloor sediment distribution, where fine sediments prevail; the only exception was observed at the eastern coastal areas, where sand con-tent reaches 70%. Contouring of granulometry statistical parameters highlights a NW towards SE transfer of fine-grain sediments. Finally, taking into account the results of the present study and all available information for the broader area, a model for the Upper Quaternary palaeogeographic evolution of the Argolis Gulf was constructed.